DURANUSITE FROM A MERCURY-ANTIMONY DEPOSIT OF CENTRAL TADZHIKISTAN - Kulikova I.M.; Vershkovskaya O.V.; Blinov V.A.; Chvileva T.N.; Gorshkov Y.N. (My University, 1988)
Until now, no descriptions of duranusite in Soviet deposits have been published. We found this mineral in a mercury-antimony deposit in central Tadzhikistan, whose ores are localized in complexly-deformed clastic rocks of Middle to Late Carboniferous age, intruded by granitoid stocks and dikes. The mineralization is controlled by a large fault, along which limestones of Middle Devonian to Early Carboniferous age are thrust over the sandstone-shale sequence. The host rocks are highly silicified, dickitized, sericitized and pyritized. The mineral composition of the area of this deposit is fairly complex and includes several successively formed paragenetic mineral associations.
Keywords: Devonian; Carboniferous; Paleozoic::Devonian; Paleozoic::Carboniferous; Палеозой::Девонская; Палеозой::Каменноугольная